Experimental foundation for natural orifice transluminal endoscopic surgery and hybrid natural orifice transluminal endoscopic surgery - Lima, Estêvão Augusto Rodrigues de (2010)
Natural orifice transluminal endoscopic surgery (NOTES) is one of the most exciting concepts that has emerged recently in the surgical field. All accesses to the abdominal cavity in the porcine model using natural orifices, e.g. transgastric, transvesical, transcolonic and transvaginal, have been described and explored. The experimental feasibility of all procedures by NOTES was successfully demonstrated in the porcine model using different types of natural orifices. However, few translations to the human have been made. NOTES is in a developmental stage and much work is still needed to refine techniques, verify safety and document efficacy. This paper is an update on the experimental foundation for NOTES and hybrid NOTES and examines the opportunities presented by this new surgical vision.